Patient-Specific Orthognathic Solutions: Expert Opinion on Guidelines and Workflow - Alf L. Nastri; Isaac Liau; Jaewon Heo; Alexander Schramm (Craniomaxillofacial Trauma & Reconstruction)
This document outlines guidelines for the use of three-dimensional virtual surgical planning in orthognathic surgery, with relevance to data acquisition, clinical diagnosis, data workflow sequencing, and operative considerations. A detailed description regarding fundamental principles of orthognathic assessment and planning is beyond the scope of this paper.